Persephin: A potential key component in human oral cancer progression through the RET receptor tyrosine kinase‐mitogen‐activated protein kinase signaling pathway. Issue 8 (23rd December 2013) - Baba, Takao; Sakamoto, Yosuke; Kasamatsu, Atsushi; Minakawa, Yasuyuki; Yokota, Satoshi; Higo, Morihiro; Yokoe, Hidetaka; Ogawara, Katsunori; Shiiba, Masashi; Tanzawa, Hideki; Uzawa, Katsuhiro
Abstract Persephin (PSPN) is a neurotrophic factor of the glial cell line‐derived neurotrophic factor (GDNF) family that promotes survival of multiple populations of neurons. Little is known about the relevance of PSPN in human malignancy including oral squamous cell carcinoma (OSCC). This study was undertaken to evaluate PSPN mRNA and protein expression by analyzing cellular proliferation and the cell cycle in PSPN knockdown cells in vitro. PSPN mRNA and protein were significantly (P < 0.05) up‐regulated in OSCC‐derived cells compared with human normal oral keratinocytes (n = 7). Cellular proliferation decreased significantly (P < 0.05) in PSPN knockdown cells with reduced receptor tyrosine kinase (RTK) signaling, and cell‐cycle arrest at the G1 phase resulted from up‐regulation of the cyclin‐dependent kinase inhibitors (p21Cip1, p27Kip1, p15INK4B, and p16INK4A). Furthermore, the PSPN protein expression in 101 primary OSCCs was significantly (P < 0.05) higher than in normal counterparts. Among the clinical variables analyzed, overexpression of PSPN also was related closely (P < 0.05) to tumoral size. Our results suggested that PSPN is a possible key regulator of OSCC progression via PSPN‐RET‐mitogen‐activated protein kinase activation and that PSPN overexpression may have diagnostic potential for OSCC. © 2013 Wiley Periodicals, Inc.